A Brontë Reading List: Part 13. (2nd October 2021) - Ogden, James; Cook, Peter; Pearson, Sara L.
Abstract : This list is part of an annotated bibliography of scholarly and critical work. The earlier parts were published in Brontë Studies, 32.2 (July 2007), 33.3 (November 2008), 34.3 (November 2009), 36.4 (November 2011), 37.3 (September 2012), 39.1 (January 2014), 41.3 (September 2016), 42.4 (November 2017), 43.4 (October 2018), 44.3 (July 2019), 44.4 (October 2019), and 45.4 (October 2020). The present part covers work published in 2018. Bibliographical details are followed where possible by summaries and assessments. Essays published in Brontë Studies are as a rule excluded, as are books reviewed in Brontë Studies ; readers are directed to the publisher's website, www.tandfonline.com, for online access. The author of each entry is indicated by the author's initials in brackets following the entry.